Beginning SharePoint 2010 : building business solutions with SharePoint - Perran, Amanda, 1976- (Programmer to programmer., 2011)
Two SharePoint MVPs provide the ultimate introduction to SharePoint 2010. Beginning SharePoint 2010: Building Team Solutions with SharePoint provides information workers and site managers with extensive knowledge and expert advice, empowering them to become SharePoint champions within their organizations. This book: provides expansive coverage of SharePoint topics, as well as specialty areas such as forms, excel services, records management, and web content management details realistic usage scenarios, and includes practice examples that highlight best practices for configuration and customization; and, includes detailed descriptions and illustrations of SharePoint's functionality. Designed to mentor and coach business and technical leaders on the use of SharePoint in addressing critical information management problems within their organizations, Beginning SharePoint 2010 is sure to become the premiere handbook for any active or aspiring SharePoint expert that highlight best practices for configuration and customization.